Development of Website-Based a Health Crisis Reporting System - Yeni Rimadeni; Hizir Sofyan; Safrizal Rahman; Setia Pramana; Rina S. Oktari (Universitas Serambi Mekkah, 2022)
Health crisis management is prioritized on health crisis risk reduction consisting of pre-health crisis stage, health crisis emergency response stage, and post-health crisis stage. Prevention and mitigation efforts at the pre-health crisis stage, in the context of our study, aim to develop an information system for health crisis management. Information system for health crisis, in general, is provided by the Health Agency. In this study, we discussed the system applied by the Health Agency of Aceh Tengah that still uses a manual information system for reporting during disasters. Hence, it causes a delay of the information updates despite the emergency situation. To overcome this problem, we proposed a newly developed health crisis management reporting system in disaster risk reduction. We used a Research and Development approach with Heuristic Review Analysis to assess the performance of the proposed system. The scope of the study was limited to the development of a new reporting system and system test on users. The research subjects were disaster officers and heads of 14 health centers involved in the health crisis reporting in Aceh Tengah. Improvements can be made in the future through trainings and system adjustments supported by institutional policies. Keywords: Health crisis, disasters, website, reporting system.